Penerapan Model Pembelajaran Team Assisted Individualization (TAI) dalam Meningkatkan Pemahaman Konsep Matematika Siswa Kompetensi Bilangan - Mashelin Wulandari; Fauziah Yolviansyah; Mia Misastri (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This research aims to improve students' understanding of mathematical concepts in number competency by using the Team Assisted Individualization (TAI) Learning Model in class IV B SDN No. 64/1 Muara Bulian. Methodology: This research is a study that consists of 2 cycles. This type of research uses a mixed method, namely a combination of quantitative and qualitative research. The research subjects were students of class IV B at SD Negeri 64/1 Muara Bulian. The data obtained are quantitative data and qualitative data. Data collection techniques were obtained through observation and interviews. Then the data were analyzed based on the type of data obtained. Main Findings: The study's findings showed that students' understanding of concepts increased from 60.35% in cycle I to 84.86% in cycle II. So that the use of the Team Assisted Individualization (TAI) learning model can help improve students' conceptual understanding of number competence in class IV B SDN NO. 64/1 Muara Bulian. Novelty/Originality of this study: The update in this research is contained in the results of this research, where the studies in this article are the latest results in the field of science, especially mathematics education. With this research, readers and other researchers can determine the impact of using the Team Assisted Individualization (TAI) learning model on students' understanding of mathematical concepts in elementary schools, especially in number competency material.